Асимптотическое решение смешанной краевой задачи для пятислойной изотропной термоупругой полосы и некоторое приложение - Л. А. Агаловян; Р. С. Геворкян; А. В. Саакян (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
By asymptotic integration of the two-dimensional equations of elasticity theory for a thermoelastic strip, the components of stress tensor and components of displacement vector are calculated in inner problem of symmetrical assembled five-layer strip, when between a parts of layers there are noncomplete contact subjected to Coulomb law of dry friction. Analysis of the special case, which can model of stress-strain state of brake pads at braking, is carried out.
Keywords: Mechanics of deformable solids; Generalities, axiomatics, foundations of continuum mechanics of solids; Elastic materials